Core–shell NaBH4@Ni Nanoarchitectures: A Platform for Tunable Hydrogen Storage. Issue 17 (13th July 2022) - Salman, Muhammad Saad; Yang, Yuwei; Zubair, Muhammad; Bedford, Nicholas M.; Aguey‐Zinsou, Kondo‐Francois
Abstract: The core–shell approach has surfaced as an attractive strategy to make complex hydrides reversible for hydrogen storage; however, no synthetic method exists for taking advantage of this approach. Here, a detailed investigation was undertaken to effectively design freestanding core–shell NaBH4 @Ni nanoarchitectures and correlate their hydrogen properties with structure and chemical composition. It was shown that the Ni shell growth on the surface of NaBH4 particles could be kinetically and thermodynamically controlled. The latter led to varied hydrogen properties. Near‐edge X‐ray absorption fine structure analysis confirmed that control over the Ni 0 /Ni x B y concentrations upon Ni II reduction led to a destabilized hydride system. Hydrogen release from the sphere, cube, and bar‐like core–shell nanoarchitectures occurred at around 50, 90, and 95 °C, respectively, compared to the bulk (>500 °C). This core–shell approach, when extended to other hydrides, could open new avenues to decipher structure–property correlation in hydrogen storage/generation. Abstract : The core–shell opportunity : Freestanding core–shell NaBH4 @Ni nanoarchitectures are designed by optimizing a simple wet‐chemistry approach. Improved hydrogen properties can be achieved by adjusting Ni deposition on the surface of NaBH4 particles and the resulting Ni 0 /Ni x B y concentration.